الجدوى الاقتصادية لاستخدام الخلايا الشمسية ووحدات الديزل لتغذية أحمال مجتمع ريفي معزول - بدور جهاد; حسن هيام (Latakia University Journal -Engineering Sciences Series, 2016)
هذه المقالة تقدم دراسة متكاملة من الناحية الفنية والاقتصادية لتغذية الأحمال الكهربائية لمجتمع ريفي معزول أو قرية صغيرة معزولة ممثلة بقرية المزرعة التابعة لبلدة نوى الواقعة إلى الشمال الغربي لمحافظة درعا بمسافة تبعد حوالي 30[Km]. إن المنهجية المتبعة لهذه الدراسة تهدف إلى المقارنة بين حالتين للأحمال الكهربائية المطلوبة ضمن سيناريو خاص لكل حالة، السيناريو الأول يمثل تغذية الأحمال الخاصة بأنشطة حياتية يومية يقوم بها سكان هذه القرية لحالة مجتمع ريفي نموذجي، السيناريو الثاني إضافة أحمال السقاية للأراضي الزراعية المحيطة إلى السيناريو الأول. لتغذية الأحمال المطلوبة تم إجراء مقارنة بين خيارين، الخيار الأول استخدام خلايا شمسية كمصدر طاقة متجددة، الخيار الثاني استخدام وحدات توليد ديزل كمصدر طاقة تقليدية. تضمنت هذه المقالة إعداد النموذج الرياضي لمنظومة العمل السابقة ومن ثم تحديد حجم هذه المنظومة لكلا من حالتي الأحمال والخيارين السابقين لمصادر الطاقة. إعداد برامج على الحاسوب للدراسة السابقة لسهولة إسقاطها على حالات مشابهة. شمل البحث أيضا دراسة اقتصادية للحالات السابقة تم التعرض من خلالها لحساب الكلفة الثابتة أو كلفة الإنشاء لمكونات منظومة العمل، حساب الكلفة المتغيرة، حساب الكلفة السنوية ومن ثم تقدير كلفة إنتاج الكيلووات الساعي والتوصل إلى تحديد البديل أو الخيار الأجدى اقتصاديا. تم استكمال هذه الدراسة بإلقاء الضوء على حجم مخلفات التلوث الذي يسببه العمل اليومي لوحدات الديزل، إبراز الأهمية الاقتصادية لاستخدام الخلايا الشمسية وخاصة في المواقع المعزولة وفي المجتمعات الريفية والزراعية كخيار اقتصادي وبدون مخلفات ضارة للبيئة. This paper introduces an integrated study concerning the technical and economical sides for supplying the electrical loads of a rural isolated society or small isolated village represented in Almazraa village relevant to Nawa Town located at the north western of Daraa Governorate at a distance of about 30[Km]. The followed methodology of this study aims at the comparison between two states required electrical loads according to special scenario of each state, the first scenario represents the feeding of special loads of a daily lifetime activity performed by the inhabitants of this village representing a case of typical rural society, and the second scenario adding the loads of irrigation of surrounding agricultural lands to the first scenario. For supplying the required loads then making a comparison between two choices, the first choice is the usage of solar cells as a renewable energy source, while the second choice is the usage of diesel generation units as a traditional energy source. This paper included the preparation of the mathematical model of previous system then to determine the volume of this system for each of the two cases of loads and the previous two choices of energy sources. The preparation of computer programs of previous study because of the easiness of projecting them two similar cases. The research also included an economical study of the previous cases then coming through them into the computation of fixed cost or construction cost, running cost and the annual cost and then estimating the production cost of Kilo Watt-hour and to identify the more economically feasible of choice. Then to complete this study by focusing on the volume mass of contamination wastes caused by the daily work of diesel units and presentation of the economical importance for the usage of solar cells especially in the isolated areas and in the rural and agricultural societies as economical choice and without an environmental damaging wastes.